INTEGRATED DISEASE MANAGEMENT OF PURPLE BLOTCH DISEASE OF ONION - B. S. CHETHANA,; G. GANESHAN,; S. R. ARCHANA,; K. BELLISHREE, (The Bioscan, 2015)
Purple blotch caused by Alernariaporri (Ellis) Ciff.is the most destructive disease commonly prevailing in onion growing areas of the world. Field experiments were conducted to evaluatethe efficacy of sequential and solo application of bioagents, botanicals and fungicides as foliar spray against purple blotch disease of onion for two consecutive seasons (2009-2010 and 2010-2011).Among the six different sequential treatments, mancozeb fol- lowed by Trichodermaharzianum and pongamia oil (Sq1) was found effective and recorded leastmean disease intensity of 25.54% and highest bulb yield of 33.01t/ha. Mancozeb (Mz-Mz-Mz) was the mosteffectivefungicide with least meandisease intensity of 22.87%and yield of 32.09t/ha. Among the bioagents and botanicalsT.harzianumand garlic extract were effective recording mean disease intensity of 28.62% and 27.34%and an yield of 29.70 t/ha and 33.03t/ha.The highestand comparatively equal cost benefit ratiowas obtained in mancozeb (1:10.18) and Sq1(mancozeb-Trichodermaharzianum- pongamia oil)The sequential application of Mancozeb-T.harzianum-Pongamia oil (Sq1)is the best IDM package reported for the first time to obtain residue free produce.By adoptingIDM package(Sq1)the usage of fungicides could be minimized to an extent of 66% and can be an economically viable substitute forthree sprays of mancozeb (Mz-Mz-Mz).